1999
DOI: 10.1002/1531-8249(199907)46:1<45::aid-ana8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Seizure control and mortality in epilepsy

Abstract: Mortality rates are increased among people with epilepsy, and may be highest in those with uncontrolled seizures. Because epilepsy surgery eliminates seizures in some people, we used an epilepsy surgery population to examine how seizure control influences mortality. We tested the hypothesis that patients with complete seizure relief after surgery would have a lower mortality rate than those who had persistent seizures. Three hundred ninety‐three patients who had epilepsy surgery between January 1986 and Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
5
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(233 citation statements)
references
References 37 publications
(70 reference statements)
9
212
5
7
Order By: Relevance
“…Previous authors also reported that late mortality was associated with persistent seizures after surgery. Sperling et al (4,12) reported that seizure-free patients had a lower mortality rate than those with persistent seizures. Vickrey (3) studied the mortality rate in patients who had diagnostic evaluations for epilepsy surgery, and found that "surgery patients" had significantly lower mortality at an average follow-up of 6 years compared with nonsurgical patients."…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors also reported that late mortality was associated with persistent seizures after surgery. Sperling et al (4,12) reported that seizure-free patients had a lower mortality rate than those with persistent seizures. Vickrey (3) studied the mortality rate in patients who had diagnostic evaluations for epilepsy surgery, and found that "surgery patients" had significantly lower mortality at an average follow-up of 6 years compared with nonsurgical patients."…”
Section: Discussionmentioning
confidence: 99%
“…5,8,82,90 Uncontrolled seizures are also associated with an elevated risk for sudden unexpected death in epilepsy (SUDEP). 32,59,75 Pharmacological approaches to reducing seizure frequency, while effective in many cases, are dependent on continued drug compliance through out the course of a person's life. Additionally, in approximately 30%-40% of patients, the epilepsy is pharmacoresistant.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…The National General Practice Study of Epilepsy (NG-PSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up (Lhatoo and Sander 2001), and the results of the Medical Research Council Antiepileptic Drug Withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission (1991). Information concerning risk factors for SUDEP is conflicting, but potential risk factors include: early adulthood, early onset of epilepsy (Nilsson et al 1999), long duration of epilepsy (Walczak et al 2001), uncontrolled seizures (mainly in those with TLE) (Walczak et al 2001, Sperling et al 1999, high seizure frequency (Walczak et al 2001, Langan et al 2005, certain seizure types (Walczak et al 2001, Kloster andEngelskjon 1999), higher numbers of AED (Nilsson et al 1999, Walczak et al 2001) and winter temperatures (Scorza et al 2007). Additionally, potential pathomechanisms for SUDEP are unknown, but it is very probable that cardiac arrhythmias during and between seizures, electrolyte disturbances, arrhythmogenic drugs or transmission of epileptic activity to the heart via the autonomic nervous system potentially play a role for SUDEP (Stollberger and Finsterer 2004).…”
Section: General Aspectsmentioning
confidence: 99%